2020
DOI: 10.1613/jair.1.12151
|View full text |Cite
|
Sign up to set email alerts
|

Modular Structures and Atomic Decomposition in Ontologies

Abstract: With the growth of ontologies used in diverse application areas, the need for module extraction and modularisation techniques has risen. The notion of the modular structure of an ontology, which comprises a suitable set of base modules together with their logical dependencies, has the potential to help users and developers in comprehending, sharing, and maintaining an ontology. We have developed a new modular structure, called atomic decomposition (AD), which is based on modules that provide strong logical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 0 publications
0
30
0
1
Order By: Relevance
“…To have a realistic mix of CIs and assertions that reflects the typical shape of the background ontology, observations in (K) were generated by selecting the given number of axioms from the background ontology, which were then removed from the background. Since in large ontologies, a fully random selection would result in an observation of unrelated axioms, we first extracted a subset of at least 100 axioms by combining randomly selected genuine modules: genuine modules are small subsets of the ontology that contain a given axiom and preserve all entailments over the signature of the subset, and thus contain only axioms that in some way interact with each other [Vescovo et al, 2011]. From these subsets of the ontology, which contained between 100 and 20,979 axioms (median 199), we generated the observations by random selection.…”
Section: Discussionmentioning
confidence: 99%
“…To have a realistic mix of CIs and assertions that reflects the typical shape of the background ontology, observations in (K) were generated by selecting the given number of axioms from the background ontology, which were then removed from the background. Since in large ontologies, a fully random selection would result in an observation of unrelated axioms, we first extracted a subset of at least 100 axioms by combining randomly selected genuine modules: genuine modules are small subsets of the ontology that contain a given axiom and preserve all entailments over the signature of the subset, and thus contain only axioms that in some way interact with each other [Vescovo et al, 2011]. From these subsets of the ontology, which contained between 100 and 20,979 axioms (median 199), we generated the observations by random selection.…”
Section: Discussionmentioning
confidence: 99%
“…Inseparability relations and their robustness properties have been introduced and studied as fundamental requirements to modules by Konev et al (2009). Further module properties have been defined and discussed in various places in the literature, mostly in the context of a specific module notion, such as self-containment and depletingness (Kontchakov et al 2009;Sattler, Schneider, and Zakharyaschev 2009;Kontchakov, Wolter, and Zakharyaschev 2010;Nortjé, Britz, and Meyer 2013a;Gatens, Konev, and Wolter 2014;Armas Romero et al 2016;Del Vescovo et al 2020), justification-preservation (Armas Romero et al 2016Peñaloza et al 2017;Chen, Ludwig, and Walther 2018;Chen et al 2019;Koopmann and Chen 2020). Del Vescovo et al (2020) identified module properties required by AD and briefly discussed those for LBMs, MEX, DBMs, and RBMs.…”
Section: Related Workmentioning
confidence: 99%
“…Decomposition aims at computing the modular structure of a TBox-a representative subset of all modules together with their logical interactions. This structure can be used to better understand the TBox, aid its collaborative design, and optimize tool support (Cuenca Grau et al 2006;Del Vescovo et al 2020). Among the available techniques, atomic decomposition (AD) (Del Vescovo et al 2011) stands out by its efficiency and genericness: the underlying algorithm is based on a linear number of module extractions, for a suitable module notion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modularization process is motivated by the problem of dealing with complex and large-scale ontologies by decomposing them into modules. Therefore, many ontology modularization approaches have been proposed, and several prototypes have been developed [7,8,17,43,61,63]. These approaches can be classified into two main categories: ontology module extraction and ontology partitioning.…”
Section: Ontology Modularizationmentioning
confidence: 99%